Perubahan Sosial dan Budaya Akibat Media Instagram bagi Kalangan Mahasiswa di Kota Medan - Erwan Efendi; Winda Kustiawan; Dodi Candra; Muhammad Ridha (Peneliti.net, 2023)
Socio-cultural changes in the world of social media, namely the use of Instagram in Medan City, especially for students, have caused changes in human behavior. The research results show that the use of Instagram also has an impact on the emergence of social and cultural changes that are happening to students in the city of Medan today. They are not shy about excessive sharing and self-disclosure in cyberspace. Of course, this culture arose because of the presence of Instagram as a social media that can be accessed by anyone. Students are no longer able to provide boundaries between private and public spaces, so that Instagram now also has an influence not only being placed in the context of a channel or medium, but Instagram is already a way of life in the relationship between users and technology.